Barriers to the enforcement of mandatory seat belt laws in Ghana: an exploratory study. (14th January 2021) - Okyere, Paul; Agyei-Baffour, Peter; Harris, Muriel Jean; Mock, Charles; Yankson, Isaac Kofi; Donkor, Peter; Owusu-Dabo, Ellis
Abstract: Road traffic accidents claim millions of lives every year across the world. Fortunately, effective safety and preventive measures such as routine maintenance of vehicles and roads and the use of seat belts exist. Yet, authorities in some countries fail to enforce laws on these measures. One of the barriers to compliance with traffic laws is poor enforcement. Using a cross-sectional study design, we explored the barriers to the enforcement of mandatory seat belt laws in Ghana. We employed an open-ended key informant interview guide to interview 26 staff of the Motor Traffic and Transport Department of the Ghana Police Service, National Road Safety Authority and the Driver and Vehicle Licensing Authority. The interviews which lasted between 30 and 45 min per session were analysed through a thematic approach facilitated by ATLAS.ti. The findings showed that the barriers to the enforcement of seat belt laws mentioned by the participants were institutional factors (inadequate resources and logistics and inability to enforce vehicle safety standards) political factors (external interference and lack of consensus on seat belt law implementation) and human factors (poor public attitudes and non- recognition of road safety as both individual and collective responsibility). The enforcement of road safety laws could be enhanced by adequately resourcing officers, addressing external interference of police duties and empowering officers to perform their duties without fear or favour. These findings are also useful in continuous public education and enhanced enforcement of the seat belt laws.